Users and Video Platforms in Relation to the New Registry of Providers under Spain’s General Audiovisual Communication Law 13/2022 - Abaurrea Velarde, Jorge; Cetina Presuel, Rodrigo (Cuadernos de Documentación Multimedia, 2025)
This article examines the establishment and functioning of Spain’s State Registry of Audiovisual Communication Service Providers, introduced by Law 13/2022 of July 7 (General Audiovisual Communication Law, LGCA), and its relationship with Directive (EU) 2018/1808 (AVMSD) and Regulation (EU) 2022/2065 (DSA). The study explores how the registry adapts to the convergent digital ecosystem, encompassing video-sharing platform service providers (PIV) and users of special relevance (UER). It outlines the legal foundations, registration procedures, transparency obligations, and the supervisory role of bodies such as the National Commission on Markets and Competition (CNMC). Furthermore, it assesses the registry’s impact on platform oversight and UER activities, addressing current challenges and future prospects, particularly regarding self-regulation, co-regulation, and user protection in the evolving digital environment.
Keywords: Registry of Providers; General Audiovisual Communication Law; AVMSD Directive; DSA Regulation; Video-Sharing Platforms; Users of Special Relevance; Audiovisual Regulation; Documentation